Turkey, Russia and Iran in the Middle East
XI, 249 p. 15 illus., 12 illus. in color.
Keywords: This book explores the complexity of the Syrian question and its effects on the foreign policies of Russia, Iran, and Turkey. The Syrian crisis has had a major effect on the regional order in the Middle East. Syria has become a territory where the rivalry between Russia and Western powers is being played out, and with the West’s gradual withdrawal, the conflict will without a doubt have lasting effects locally and on the international order. This collection focuses on the effects of the Syrian crisis on the new governance of the Middle East region by three political regimes: Russia, Iran, and Turkey. Many articles and a number of books have been written on this conflict, which has lasted over ten years, but no publication has examined simultaneously and comparatively how these three states are participating in the shared management of the Syrian conflict. Bayram Balci, CNRS/CERI Sciences Po Paris, Institut Français d’Etudes Anatoliennes, Istanbul, Turkey. Balci works on religion and politics in Turkey, Central Asia, and the Middle East. Nicolas Monceau is Associate Professor of Political Science, University of Bordeaux, France. His research focuses on Turkish politics and Turkey in its regional and international environment. He has published several books on Turkey and the EU as well as the Turkish elite.